STATUS POPULASI DAN KONSERVASI BEKANTAN (Nasalis larvatus Wurmb. 1787) DI HABITAT RAWA GELAM, KALIMANTAN SELATAN - Sofian Iskandar; Hadi S. Alikodra; M. Bismark; Agus P. Kartono (Pusat Penelitian dan Pengembangan Hutan, 2017)
ABSTRACTA study on population of proboscis monkey (Nasalis larvatus Wurmb.) was conducted in the area of riparian ecosystem of Rawa Gelam, Tapin District, South Kalimantan duringthe period of February-March 2014. The purpose of this study was to determine the condition and the structure of the proboscis monkey population living outside the forest area. Rawa Gelam ecosystem is a cultivation area located on riverbanks of the Puting river. The remaining vegetation at Rawa Gelam contains only a maximum of 200 meters in width, and behind it there were paddy fields and palm oil plantations. The population of proboscis monkeys was counted using Total Count Sampling method. Result of this study showed that the population of proboscis monkeys in Rawa Gelam consisted of nine groups, with the total number of individuals was 192. The population density was 28.34 individuals/km2 with a group density of 1.34 groups/km2. In addition to this species, Rawa Gelam habitat was also inhabited by two other primate species. Seven groups of long-tailed macaques (Macaca fascicularis) and five groups of langurs (Trachyphitecus auratus) were recorded from this area, with the number of individuals of 47 and 76, respectively. The main threat of proboscis monkey's conservation in Rawa Gelam was habitat destruction and change of habitat function. Proboscis monkeys can be saved from the local extinction through habitat restoration needs to be done by applying agroforestry system and developing integrated ecotourism development.Keywords: Conservation, Nasalis larvatus, proboscis monkey, population, Rawa Gelam.ABSTRAKPenelitian populasi bekantan dilakukan di kawasan ekosistem riparian Rawa Gelam, Kabupaten Tapin, Kalimantan Selatan pada bulan Februari-Maret 2014. Tujuan penelitian ini adalah untuk mengetahui kondisi populasi dan struktur kelompok bekantan yang hidup di luar kawasan hutan. Kawasan ekosistem Rawa Gelam merupakan lahan budidaya yang terletak di kanan-kiri Sungai Puting. Vegetasi Rawa Gelam yang tersisa hanya selebar maksimal 200 meter dan di belakangnya terdapat persawahan dan kebun kelapa sawit. Penghitungan populasi bekantan dilakukan dengan metode Total Count Sampling. Berdasarkan hasil penelitian, diketahui populasi bekantan di Rawa Gelam sebanyak sembilan kelompok bekantan, dengan jumlah 192 individu. Kepadatan populasi bekantan di kawasan ekosistem Rawa Gelam adalah 28,34 individu/km2 dengan kepadatan kelompok 1,34 kelompok/km2. Selain bekantan, kawasan Rawa Gelam juga dihuni oleh dua jenis primata lainnya, yaitu Monyet Ekor Panjang (Macaca fascicularis) dan Lutung Hitam (Trachyphitecus auratus). Tercatat ada lima kelompok Lutung Hitam dengan jumlah 47 individu dan tujuh kelompok monyet ekor panjang dengan jumlah 76 individu. Ancaman utama konservasi bekantan di Rawa Gelam adalah perusakan habitat dan perubahan fungsi kawasan. Untuk menyelamatkan bekantan dari kepunahan lokal, perlu dilakukan restorasi habitat dengan menerapkan pola agroforestridan pengembangan ekowisata terpadu.Kata kunci: Konservasi, Nasalis larvatus, bekantan, populasi, Rawa Gelam.